Evaluating the Food Profile in Qatar within the Energy–Water–Food Nexus Approach - Odi Fawwaz Alrebei; Tareq Al-Ansari; Mohammad S. Al-Kuwari; Abdulkarem Amhamed (Foods, 2023)
Finding a balance between the capacity for production and the rising demand for food is the first step toward achieving food security. To achieve sustainable development on a national scale, decision-makers must use an energy, water, and food nexus approach that considers the relationships and interactions among these three resources as well as the synergies and trade-offs that result from the way they are handled. Therefore, this paper evaluates the Energy–Water–Food Nexus Profile of Qatar at a superstructural level by applying the Business-As-Usual (BAU) storyline; thus, trends of past data have been used to provide future projections to 2050 using the statistical prediction tools such as the compound annual growth rates of food demand (<semantics>CAGRFD</semantics>), international supply (<semantics>CAGRFI</semantics>), and the average local food supply change factor (<semantics><mover accent="true">c¯</mover></semantics>). Once the BAU storyline has been generated, the source-to-demand correlations have been defined for each food category. Such correlations include the annual and average ratios of the local food supply to the total demand (i.e., <semantics>αi</semantics> and <semantics><mover>α¯</mover></semantics>) and the ratios of the local food supply to the international supply (i.e., <semantics>βi</semantics> and <semantics><mover>β¯</mover></semantics>). In addition, as an effort to identify the required action to reach food self-sustainability, the additional local food supply to achieve (<semantics>xi,add)</semantics> and its ratio to the local demand (<semantics>γ</semantics>) have been defined. The highest average ratio of the local food supply to the total demand (<semantics>αi</semantics>) was found for the meat category, which was estimated to be 48.3%. Finally, to evaluate the feasibility of attaining food self-sustainability in Qatar, the water consumption (<semantics>Vw,i</semantics>) and its corresponding required energy for each food category have been estimated.